2020
DOI: 10.1007/s12223-020-00836-y
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ®-based quantitative proteomics reveals the proteomic profiling of methicillin-resistant Staphylococcus aureus-derived extracellular vesicles after exposure to imipenem

Abstract: This study sought to reveal the proteomic profiling of methicillin-resistant Staphylococcus aureus (MRSA)-derived extracellular vesicles (EVs) after exposure to imipenem. The advanced isobaric tags for relative and absolute quantitation (iTRAQ®) proteomic approach were used to analyze the alterations in MRSA-derived EV protein patterns upon exposure to imipenem. A total of 1260 EV proteins were identified and quantified. Among these, 861 differentially expressed exosome proteins (P < 0.05) were found. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Complete identification of exosomal protein cargo can be achieved with a "global discovery" approach using multidimensional fractionation strategies followed by high-resolution mass spectrometric (MS) [326], which could include a quantitative cargo analysis if desired. This quantification can be performed with the Stable Isotope Labeling by Amino acids in Cell culture (SILAC) or Isobaric Tag for Relative and Absolute Quantitation (iTRAQ) methods, involving the incorporation of a stable heavy isotope-labeled amino acid into the peptides of interests [327,328]. However, these are expensive protocols, and the peptide of interest is not always known.…”
Section: Methods For the Study Of Exosomal Contentmentioning
confidence: 99%
“…Complete identification of exosomal protein cargo can be achieved with a "global discovery" approach using multidimensional fractionation strategies followed by high-resolution mass spectrometric (MS) [326], which could include a quantitative cargo analysis if desired. This quantification can be performed with the Stable Isotope Labeling by Amino acids in Cell culture (SILAC) or Isobaric Tag for Relative and Absolute Quantitation (iTRAQ) methods, involving the incorporation of a stable heavy isotope-labeled amino acid into the peptides of interests [327,328]. However, these are expensive protocols, and the peptide of interest is not always known.…”
Section: Methods For the Study Of Exosomal Contentmentioning
confidence: 99%
“…Concerning EV composition, a recent study by Briaud et al demonstrated that temperature variations affect the EV protein and RNA cargo quantitatively and qualitatively, which is also reflected in different EV cytolytic activities towards host cells [40]. Culture media, growth phase, and antibiotic treatment were also shown to alter S. aureus EV content [39,[43][44][45]. However, studies comparing the impact of different environmental conditions on both S. aureus producing cells and its derived EVs are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These DEGs were all related to the synthesis of ribosomal proteins, which in turn affected the translation machinery and led to bacterial death. [48][49][50][51] Both of them mRNA expression of DEGs were down regulated, and the gene regulation effect of NPs was more prominent than that of BBR, resulting in the antibacterial effect of NPs was far superior to BBR. Besides, most of these DEGs could also be found in GA group.…”
mentioning
confidence: 99%